Pengaruh Teknik Rebozo Terhadap Lamanya Kala I Dalam Persalinan Pervaginam Di Klinik Eliza Bestari - Sitorus, Ririn Anggriani; Selvi Puspan Sari; Debby Pratiwi (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Childbirth is the process of movement of the fetus, placenta and membranes from the uterus through the birth canal. This process starts with the opening and dilatation of the cervix which is caused by uterine contractions with regular frequency, duration and strength. One effort to speed up the birthing process can be done with complementary methods, one of which is the rebozo technique. To determine the effect of the Rebozo technique on the length of the first stage in vaginal delivery at the Eliza Bestari Clinic. This research is a type of Quasi-Expermental research with a One Group Pretest Posttest design. In this design, before the treatment is given, the sample is first given a pretest (initial test) and after the experiment the sample is given a posttest (final test). Based on the results of data analysis, it can be explained that before the rebozo technique was carried out, the majority of primigravida mothers experienced a long duration of the first stage of the slow active phase, namely 18 hours with an SD value of 10.642 and after the rebozo technique was carried out the majority of respondents experienced a long duration of the first stage of the fast active phase, namely 4 hours with an SD value of 4.205. The results of the Wilchoxon test analysis show that the p value is 0.028 (p < α 0.05) which means that there is a significant influence of the Rebozo Technique on the Length of the First Stage in Vaginal Delivery. From the research and discussion that has been carried out, it can be concluded that there is a significant influence of the Rebozo Technique on the Length of the First Stage in Vaginal Delivery at the Eliza Bestari Clinic.